FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - sayidah, nur (Jurnal Analisa Akuntansi dan Perpajakan, 2017)
The purpose of this study is to test effect of profitability, leverage, firm size and age to level of disclosure of CSR (corporate social responsibility). CSR is measured by using the checklist data from the Global Reporting Index (GRI). Profitability is measured by using net profit margin (NPM). Leverage is measured by using the debt ratio.  The proxy of firm size is logarithm of total assets. Firm age is the time since its establishment until the years of research. Sample selection is done by purposive sampling method. The criteria used are companies from the mining industry,  published its annual report for three consecutive years, and using rupiahs as unit of currency. Regression analysis showed that four variables simultaneously affect the level of CSR disclosure. Partial analysis showed only two variables including size and age that affect the level of disclosure of CSR